2004
DOI: 10.1348/000712604322779442
|View full text |Cite
|
Sign up to set email alerts
|

Improving balance by performing a secondary cognitive task

Abstract: Contrary to general findings in the attention and memory literature, some studies have shown that performing a secondary cognitive task produces an improvement in balance performance. The purpose of the present experiment was to investigate under what condition such an improvement would occur. Young and older adults were asked to hold as still as possible on a platform that measured sway while performing or not performing the encoding phase of the Brooks' (1967) spatial or non-spatial memory task. The difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 11 publications
10
88
1
1
Order By: Relevance
“…For instance, in support of the attention resource competition view, Andersson et al [2] found that performing a concurrent visuospatial search task decreased balance performance in middle-aged adults (M age = 40.4 years) under a challenging condition with attenuated proprioceptive sensory inputs (i.e., standing on a sway-referenced platforms). However, other studies found that performing a concurrent cognitive task while standing actually enhanced postural control [1,4,[8][9][10][11]14,51,52,63,70,76]. For example, examining the effects of a variety of working memory tasks including a visuospatial task, Dault et al [8] found reduced center of body pressure (COP) displacements in young adults (M age = 23.0) under dual-task situations compared to the single-task condition regardless of the difficulty of the postural control task.…”
Section: Dual-task Attentional Sharing Between Postural Control and Cmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, in support of the attention resource competition view, Andersson et al [2] found that performing a concurrent visuospatial search task decreased balance performance in middle-aged adults (M age = 40.4 years) under a challenging condition with attenuated proprioceptive sensory inputs (i.e., standing on a sway-referenced platforms). However, other studies found that performing a concurrent cognitive task while standing actually enhanced postural control [1,4,[8][9][10][11]14,51,52,63,70,76]. For example, examining the effects of a variety of working memory tasks including a visuospatial task, Dault et al [8] found reduced center of body pressure (COP) displacements in young adults (M age = 23.0) under dual-task situations compared to the single-task condition regardless of the difficulty of the postural control task.…”
Section: Dual-task Attentional Sharing Between Postural Control and Cmentioning
confidence: 99%
“…A review of the literature suggests that the interactions between mental processes and postural control can be modulated by factors such as stimulus and response modalities (e.g., [10,61,62,80]), difficulty of the concurrent secondary task (see [72], for review), postural constraints affecting the difficulty of the postural task (e.g., [9,19,50,68,79], individual differences in sensorimotor expertise (e.g., [68]), and aging (e.g., [11,14,22,25,28,32,36,63]). A number of studies considered the influence of experimental procedural factors of the concurrent task (e.g., stimulus presentation and response modes) on posture control.…”
Section: Potential Factors Affecting Resource Sharing Between Posturamentioning
confidence: 99%
See 2 more Smart Citations
“…Interpretation of whether performance is improved or impaired may be difficult for some postural measures. For example, several studies have reported that carrying out a cognitively demanding task can lead to a reduction in postural sway during upright standing, especially for older adults [11,28]. One interpretation of this is that increased cognitive activity improves postural control as it removes overt attention from an 'overly automised' postural activity [4].…”
Section: Verbal Fluencymentioning
confidence: 99%